2008 IEEE Asia-Pacific Services Computing Conference 2008
DOI: 10.1109/apscc.2008.64
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Interface Usability of B2C Hypermarket E-commerce Website

Abstract: In order to serve the on-line users who do shopping for 24 hours, the on-line shopping systems platform is more complicated than traditional one. Therefore, the user interface usability problems become a critical issue. Take the Yahoo!kimo shopping mall as a test platform. In this paper, the data collection method of thinking-aloud was adopted to record the participants. The video images and verbal protocols were transcribed, segmented and bottom-up coded. 121 problems concerning usability could be classified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…Although design principles have been suggested for user interfaces in a variety of technological environments, including computer-assisted instruction platforms (Seo and Woo 2010), websites (Hu et al 2008;Corry et al 1997), cell phones (Lee et al 2006), and electronic books (Chong et al 2009;Wilson and Landoni 2003), few researchers have specifically considered principles for enhancing the design of user interfaces for digital textbooks used in classroom settings. This study identified four usability attributes for the digital textbook platform: learnability, efficiency, effectiveness, and satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although design principles have been suggested for user interfaces in a variety of technological environments, including computer-assisted instruction platforms (Seo and Woo 2010), websites (Hu et al 2008;Corry et al 1997), cell phones (Lee et al 2006), and electronic books (Chong et al 2009;Wilson and Landoni 2003), few researchers have specifically considered principles for enhancing the design of user interfaces for digital textbooks used in classroom settings. This study identified four usability attributes for the digital textbook platform: learnability, efficiency, effectiveness, and satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Dix et al (1998) suggest, for instance, that the design factors contributing to increased learnability include predictability, consistency, familiarity, generalizability, and synthesizability, so to facilitate learnability, the user interface should be designed to meet the user's expectations and be consistent in terms of function and visual display (Baxley 2003;Nielsen 1993). To increase efficiency, the interface should be designed to minimize the user's memory load and help the experienced user operate the system with flexibility and speed (Ardito et al 2006;Hu et al 2008). To increase effectiveness, the interface should be designed to prevent errors, enable prompt recovery from errors, provide adequate feedback or help in problem solving, and make the internal operations of the system observable to users (Ardito et al 2006;Hu et al 2008).…”
Section: Usability Design Elements For the Digital Textbook Platform mentioning
confidence: 99%
See 1 more Smart Citation
“…Taking Yahoo Kimo as the research subject, Hui-Jiun Hu [14] collected data by asking the participants to think aloud. After transcribing, splitting, and coding the data, the scholar figured out 121 problems concerning usability.…”
Section: Existing Studies On the Usability Of E-commerce Ui Designmentioning
confidence: 99%
“…Many publications report usability problems of B2C sites [3][4][5][6][7][8], and in particular of Web-based travel and reservation systems [9][10][11][12][13][14].…”
Section: Previous Researchmentioning
confidence: 99%